2019
DOI: 10.1080/17474124.2019.1685871
|View full text |Cite
|
Sign up to set email alerts
|

Identification and management of pancreas divisum

Abstract: Pancreas divisum, the most common congenital malformation of the pancreas, occurs due to a failure of fusion of the ductal systems of the dorsal and ventral pancreatic buds in the seventh week of intra-uterine life. This leads to a dominant dorsal pancreatic duct draining though the minor papilla and a small ventral pancreatic duct draining through the major papilla. The prevalence in western populations is about 10% and more than 95% of these patients are without pancreatic symptoms, with the anomaly found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 129 publications
1
61
0
1
Order By: Relevance
“…Success rates were reported to be 76 %, 52 %, and 48 % for patients with RAP, CP and CAP, respectively. Important to note is that if strict objective outcome measures were used, instead of subjective measurements like self-reported pain or opioid usage, a smaller percentage of the patients reached clinical success in this review 17 , which is in line with the outcome of our current study.…”
Section: Discussionsupporting
confidence: 82%
“…Success rates were reported to be 76 %, 52 %, and 48 % for patients with RAP, CP and CAP, respectively. Important to note is that if strict objective outcome measures were used, instead of subjective measurements like self-reported pain or opioid usage, a smaller percentage of the patients reached clinical success in this review 17 , which is in line with the outcome of our current study.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, acute and chronic pancreatitis and associated pancreatic injury are risk factors for the development of pancreatic cancer (Becker et al, 2014;Kirkegård et al, 2018). In this context, it has been reported that pancreas divisum acts as modulator of pancreatitis risk in carriers of additional genetic variants such as the one described here in the CFTR gene (Bertin et al, 2012;Gutta et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…Pancreas divisum represents the most common congenital anomaly in pancreatic ductal anatomy in which two distinct dorsal (duct of Santorini) and ventral ducts (Wirsung duct) fail to fuse. This condition may occur in approximately 10% of the population [5] . In such cases, the dorsal duct plays the main role in drainage of pancreatic secretions through minor papilla and a small ventral duct opens to the major papilla [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic therapy includes endoscopic interventions include minor papillotomy, trans minor papilla dorsal duct stenting, and balloon dilation of the minor papilla. A surgical minor papilla procedure such as surgical sphincteroplasty is reserved for patients who fail endotherapy [5] .…”
Section: Discussionmentioning
confidence: 99%